Advances in Catalytic Depolymerization of Lignin. Issue 40 (21st October 2022) - Wan, Zhouyuanye; Zhang, Hongjie; Guo, Yanzhu; Li, Haiming
Abstract: The depletion of traditional fossil energy sources and increasing environmental concerns have sparked continued interest in the development and utilisation of renewable energy sources. Lignin is a renewable resource with an abundant aromatic ring structure and low price. However, the complex structure and low reactivity of lignin limit the development of its application. The depolymerization of lignin is considered to be an effective solution to this dilemma. The catalytic depolymerization of lignin allows the preparation of value‐added fine chemicals, such as monophenols and high‐grade biofuels, partially replacing some products based on petroleum resources. In order to produce biofuels and value‐added chemicals on a large scale through lignin depolymerization, it is necessary to develop efficient catalysts and mature catalytic systems. This review provides an overview of recent advances in catalytic depolymerization of lignin, both in terms of biocatalytic and chemical methods, respectively. Biocatalytic methods depolymerize lignin through the action of fungi, bacteria and enzymes. Chemical methods for depolymerization of lignin include pyrolysis, acid catalysis, base catalysis, oxidative catalysis, hydrogenolysis, photocatalysis, and electrocatalysis. In addition, through a detailed discussion of catalyst types, reaction mechanisms and product properties, we summarise the current opportunities and challenges for the catalytic conversion of lignin and provide an outlook on future developments in this field. Abstract : In recent years, methods for the depolymerization of lignin have been widely explored. This review presents different approaches to the catalytic depolymerization of lignin, both biocatalytically and chemically, and illustrates the reaction mechanisms and depolymerization products depending on the catalysts used.